Chemical mediation of mutualistic interactions between macroalgae and mesograzers structure unique coastal communities along the western Antarctic Peninsula. Issue 1 (6th December 2013) - Amsler, Charles D.; McClintock, James B.; Baker, Bill J.; Graham, M.
<x xml:space="preserve">Abstract</x> Hard bottom communities along the western Antarctic Peninsula region are dominated by thick macroalgal forests, which support high densities of mesograzers, particularly amphipods, and also numerous gastropods. The macroalgae are chemically defended from consumption by the mesograzers and other herbivores and they provide the mesograzers a chemically defended refuge from predation by omnivorous fish. The macroalgae benefit in return because the mesograzers remove epiphytic algae from them. Since these two assemblages are major components of the community, this can be viewed as a community‐wide mutualism. Most subcomponents of these interactions have also been documented in lower latitude communities and the similarities and differences between the communities in Antarctica and in other regions are discussed.